Development of Augmented Reality Based Learning Media to Introduce Computer Components to students in Senior High School - Ginting, Subhan Hafiz Nanda; Singh , Bodhisatva; Zhang , Jiazhen (International Journal of Educational Insights and Innovations, 2025)
This research aims to develop Augmented Reality (AR) based learning media as an educational tool to introduce computer components to high school students. AR technology was chosen because of its ability to present information interactively and realistically, so that it can improve concept understanding and motivate students in learning technical material. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). In the development stage, the AR application was designed to visualize computer components in three dimensions (3D), equipped with function descriptions and interactive animations. Product testing was carried out through validation by media experts and material experts, as well as a limited trial to class XI students majoring in Computer and Network Engineering (TKJ) in one of the high schools in Medan City. Data was obtained through questionnaires to measure media feasibility and interviews to evaluate students' responses to the application. The results showed that this AR-based learning media was very valid with an average score of 91% in the expert validation test and received positive responses from students with a satisfaction level of 89%. The use of AR applications is proven to be able to improve students' understanding of computer components, as evidenced by an increase in pretest to posttest scores by 35%. In conclusion, this AR-based learning media is effective and feasible to use as an educational tool in high schools, especially in the introduction of computer components.